Syngeneic Syrian hamster tumors feature tumor-infiltrating lymphocytes allowing adoptive cell therapy enhanced by oncolytic adenovirus in a replication permissive setting. (3rd May 2016) - Siurala, Mikko; Vähä-Koskela, Markus; Havunen, Riikka; Tähtinen, Siri; Bramante, Simona; Parviainen, Suvi; Mathis, J. Michael; Kanerva, Anna; Hemminki, Akseli
ABSTRACT: Adoptive transfer of tumor-infiltrating lymphocytes (TIL) has shown promising yet sometimes suboptimal results in clinical trials for advanced cancer, underscoring the need for approaches improving efficacy and safety. Six implantable syngeneic tumor cell lines of the Syrian hamster were used to initiate TIL cultures. TIL generated from tumor fragments cultured in human interleukin-2 (IL-2) for 10 d were adoptively transferred into tumor-bearing hamsters with concomitant intratumoral injections of oncolytic adenovirus (Ad5-D24) for the assessment of antitumor efficacy. Pancreatic cancer (HapT1) and melanoma (RPMI 1846) TIL exhibited potent and tumor-specific cytotoxicity in effector-to-target (E/T) assays. MHC Class I blocking abrogated the cell killing of RPMI 1846 TIL, indicating cytotoxic CD8 + T-cell activity. When TIL were combined with Ad5-D24 in vitro, HapT1 tumor cell killing was significantly enhanced over single agents. In vivo, the intratumoral administration of HapT1 TIL and Ad5-D24 resulted in improved tumor growth control compared with either treatment alone. Additionally, splenocytes derived from animals treated with the combination of Ad5-D24 and TIL killed autologous tumor cells more efficiently than monotherapy-derived splenocytes, suggesting that systemic antitumor immunity was induced. For the first time, TIL of the Syrian hamster have been cultured, characterized and used therapeutically together with oncolytic adenovirus for enhancing the efficacy of TIL therapy. Our results support human translation of oncolytic adenovirus as an enabling technology for adoptive T-cell therapy of solid tumors.